Antarctic subglacial drilling rig: Part I. General concept and drilling shelter structure. Issue 84 (29th April 2021) - Talalay, Pavel; Sun, Youhong; Fan, Xiaopeng; Zhang, Nan; Cao, Pinlu; Wang, Rusheng; Markov, Alexey; Li, Xingchen; Yang, Yang; Sysoev, Mikhail; Liu, Yongwen; Liu, Yunchen; et al.
Abstract: Drilling to the bedrock of ice sheets and glaciers offers unique opportunities for examining the processes occurring in the bed. Basal and subglacial materials contain important paleoclimatic and paleoenvironmental records and provide a unique habitat for life; they offer significant information regarding the sediment deformation beneath glaciers and its effects on the subglacial hydraulic system and geology. The newly developed and tested Antarctic subglacial drilling rig (ASDR) is designed to recover ice and bedrock core samples from depths of up to 1400 m. All of the drilling equipment is installed inside a movable, sledge-mounted, temperature-controlled and wind-protected drilling shelter and workshop. To facilitate helicopter unloading of the research vessel, the shelter and workshop can be disassembled, with individual parts weighing <2–3 tons. The entire ASDR system weighs ~55 tons, including transport packaging. The ASDR is designed to be transported to the chosen site via snow vehicles and would be ready for drilling operations within 2–3 d after arrival. The ASDR was tested during the 2018–2019 summer season near Zhongshan Station, East Antarctica. At the test site, 2-week drilling operations resulted in a borehole that reached bedrock at a depth of 198 m.